A cyclic dodecanuclear cobalt cluster based on a derivative of the rhodamine 6G dye with unusual magnetization1. Issue 64 (18th August 2015) - Xu, Hong; Wang, Qian; Qin, Jian-Hua; Zang, Shuang-Quan; Langley, Stuart K.; Murray, Keith. S.; Moubaraki, Boujemaa; Batten, Stuart R.; Mak, Thomas C. W.
<x xml:space="preserve">Abstract</x> A novel cyclic dodecanuclear cluster [CoII12(L)6(OH)6(Ac)6]·2DMF (1) decorated by a rhodamine 6G derivative (H2L) presents dominant intracluster antiferromagnetic interactions with S-shaped M vs. H plots.